Common Ownership and Competition: Evidence from Ultimate Owners of Private and Public Firms - Heiland, Inga (The Review of Corporate Finance Studies, 2025)
Abstract Firms under common ownership have incentives to soften competition. I exploit unique data from Norway to document the economy-wide extent of common ownership, covering private and public firms and the universe of shareholders. Using exogenous variation in common ownership at the firm-household level due to marriages among individual shareholders, I show that firms experiencing an increase in common ownership due to a marriage increase profit margins by 7 to 16 percentage points, compared to firms affected by similar marriages that do not experience a change in common ownership. (JEL: G32, L22, L26)